Sostenibilidad financiera y estrategias de recaudación de la Cooperativa de Ahorro y Crédito San Martin de Tisaleo Ltda. año 2024 - Solís Llaulle, Ricardo Javier (2025)
This research focuses on a comprehensive analysis of the collection strategies and financial sustainability of the San Martín de Tisaleo Ltda. Savings and Credit Cooperative through 2024. Its premise is the application of innovative and effective methodologies, which will contribute to continued development and positively influence the institution's economic stability. Furthermore, identifying the main internal and external factors will allow us to understand the cooperative's ability to maintain its financial sustainability, and obtaining statistical results will allow us to understand the intrinsic relationship between collection strategies and improved financial indicators. The results show that effective collection strategies, accompanied by the participation of the cooperative's active members, significantly contribute to reducing delinquency, increasing revenue, and improving economic conditions. Therefore, it can be concluded that the success of financial sustainability depends on innovation in its collection strategies and the active involvement of members, shareholders, and employees. Finally, it is advisable to strengthen these strategies, diversify revenue sources, and promote financial education to ensure the institution's long-term stability and growth.